Use of Botulism Antitoxin Heptavalent (A, B, C, D, E, F, G)—(Equine) (BAT®) in Clinical Study Subjects and Patients: A 15-Year Systematic Safety Review - Geraldine S. Parrera; Hugo Astacio; Priya Tunga; Deborah M. Anderson; Christine L. Hall; Jason S. Richardson (Toxins, 2021)
Botulism is a rare, sometimes fatal paralytic illness caused by botulinum neurotoxins. BAT® (Botulism Antitoxin Heptavalent (A, B, C, D, E, F, G)—(Equine)) is an equine-derived heptavalent botulinum antitoxin indicated for the treatment of symptomatic botulism in adult and pediatric patients. This review assesses the cumulative safety profile for BAT product from 2006 to 2020, using data received from clinical studies, an expanded-access program, a post-licensure registry, spontaneous and literature reports. The adverse event (AE) incidence rate for BAT product was calculated conservatively using only BAT product exposures for individuals with a record (512) and was alternatively estimated using all BAT product exposure data, including post-licensure deployment information (1128). The most frequently reported BAT product-related AEs occurring in greater than 1% of the 512–1128 BAT product-exposed individuals were hypersensitivity, pyrexia, tachycardia, bradycardia, anaphylaxis, and blood pressure increase reported in 2.3–5.1%, 1.8–3.9%, 1.0–2.2%, 0.89–2.0%, 0.62–1.4%, and 0.62–1.4%, respectively. For patients properly managed in an intensive care setting, the advantages of BAT product appear to outweigh potential risks in patients due to morbidity and mortality of botulism. AEs of special interest, including bradycardia, hemodynamic instability, hypersensitivity, serum sickness, and febrile reactions in the registry, were specifically solicited.